2013
DOI: 10.1163/15718174-20210005
|View full text |Cite
|
Sign up to set email alerts
|

Using Weber’s Rechtssoziologie to Explain Western Punishment: A Typological Framework

Abstract: An interdisciplinary comparative-historical fi-amework is proposed to map the relationship between legal institutional differences and the use of incarceration. The oft-cited empirical trend that Western countries cluster on an assortment of social, political, and economic outcomes is incorporated with Weberian sociology of law. Incarceration levels vary, in descending order, as a function of the institutional possibilities within the common, Roman, and Nordic law families. A country's legal origin supports ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Katherine Beckett and Bruce Western (2001) in the USA and Michael Cavadino and Paul Dignan (2006) in the UK have demonstrated that governments have relatively consistent incarceration and welfare policies as an overall strategic response to social marginality. More recently, I have argued elsewhere that the western countries follow three primary punishment regime types according to their levels of adversarialism, discretion, and public punitivism (DeMichele, 2013). Community corrections in more inclusive jurisdictions seem to be quicker to implement evidence-based changes.…”
Section: Organizational Studies and Community Correctionsmentioning
confidence: 99%
“…Katherine Beckett and Bruce Western (2001) in the USA and Michael Cavadino and Paul Dignan (2006) in the UK have demonstrated that governments have relatively consistent incarceration and welfare policies as an overall strategic response to social marginality. More recently, I have argued elsewhere that the western countries follow three primary punishment regime types according to their levels of adversarialism, discretion, and public punitivism (DeMichele, 2013). Community corrections in more inclusive jurisdictions seem to be quicker to implement evidence-based changes.…”
Section: Organizational Studies and Community Correctionsmentioning
confidence: 99%
“…All industrialized countries have professional services that arrest, prosecute, incarcerate, and supervise individuals in the community. But, there are important differences in how these functions are carried out that have profound impacts on the amount (DeMichele, ; Lacey, ; Nelkin, ) and type of punishment (Pratt and Eriksson, ; Whitman, ). In the Danish system, some people sentenced to prison are allowed to apply to serve their sentence in the community under electronic monitoring supervision.…”
Section: Comparative Research For Policy Transfermentioning
confidence: 99%
“… See Neapolitan (2001),Sutton (2000Sutton ( , 2004, andRuddell (2005) for thorough surveys of the research that empirically investigates these standard theoretical frameworks.3Durkheim (1895) andWeber (1922) were among the first to posit crime and imprisonment as shaped by socio-institutional structures.Rusche and Kirchheimer (1939) influencedFoucault (1975), who popularized this perspective and research agenda.4 See alsoSpamann (2010) andDeMichele (2013DeMichele ( , 2014.at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1744137418000127Downloaded from https://www.cambridge.org/core.…”
mentioning
confidence: 99%